Applicability of Manufacturing Lean Tools in Service Operations - Sorooshian, Shahryar; Tan, Ai Fen (IAEME Publication, 2017)
Lean manufacturing is a philosophy with fewer wastes which acts as the role to seek for minimizing unnecessary time, material and efforts in the production processes. Although lean tools have been used in the manufacturing industry since a long time ago, they are new for service industry. From previous studies, it shows there is a lot of waste in a service operations and it has a huge impact on reducing productivity. Thus, this research is carried out to rank the applicability of the lean tools to practice in the service operation/industry. This research used multi-attribute decision-making methods with the used of expert panels. A framework for applicability of lean tools in service industries is provided by this research, The framework will be useful for the industry practitioners and advisors. It is among the first lean tools applicability frameworks in service operation/industry.